Hearing protection use among aircraft maintenance trainees in University Kuala Lumpur - Mohd Ismawee, Abdul Malik (2018)
Aircraft maintenance workers are at high risk of noise induced hearing loss due to noise exposure during work. Hazards generated from workplace noise in aviation industry such as from operated aircraft engines can affect work effectiveness and increase work stress among employees as well as increase accident rate. The research objectives were to examine the relationships between risk perception, knowledge of noise hazards, knowledge of hearing protection and self-efficacy with hearing protection devices (HPDs) used among students during their industrial training. This quantitative study utilized a questionnaire consisting of26 questions to measure the relationships between safety risk perceptions, knowledge on noise hazard, knowledge of hearing protection and self-efficacy with HPDs use. A total of 132 questionnaires were distributed and 10 1 were returned yielding a response rate of 76%. Data collection was carried out using stratified random sampling techniques. The Pearson correlation analysis showed that there were positive and significant (p=0.01) relationships where knowledge on hearing protection was high with r = 0.776, self-efficacy was moderate with r = 0.612, knowledge on noise hazards was moderate with r=0.564, and risk perception was low with r=0.403 towards HPDs use. Multiple regression test showed knowledge on hearing protection was the most influential variable towards HPDs use. All independent variables accounted for 67.7% of the variance in HPDs used. Recommendations and suggestions for future research were also discussed.